Swedish phrasal verbs and their aspectuality in comparison to Croatian verbal aspect - Novak Milić, Jasna (Array, 2012)
When describing phrasal verbs in Swedish, many linguists name aspect as one of the verbal particle’s important characteristics (Teleman 1972, Lindvall 1999). Some even identify Swedish (Germanic) verbal particles with Slavic verbal prefixes, i.e. claim that Swedish verbal particles have the same function(s) as Slavic verbal prefixes (Lindvall 1998). Others, on the other hand, claim that the Slavic type of aspect, defined as a morphological and/or grammatical category does not exist in Swedish (Norén 1996). In attempt to resolve the existing disaccord and to get a better insight into Swedish phrasal verbs in comparison to Croatian prefixed verbs and their aspect, the author conducted research based on data that was collected from five Swedish novels and their Croatian translations. Altogether 6, 472 Swedish sentences and their Croatian translations were analyzed. Three types of relations were investigated: a) Swedish phrasal verbs vs. Croatian (im)perfective verbs, b) the meaning and function of Swedish particles vs. the meaning and function of Croatian prefixes, c) definite objects in Swedish sentences vs. Croatian perfective verbs (Verkuyl 1972, 1993). The analysis shows that both languages have the ability to express the same aspectual meanings using partially different means. Whereas both languages have the categories of inherent verbal meaning, aktionsart and aspectuality, only Croatian has verbal aspect, a grammatical category which differentiates perfective from imperfective verbs. The hypothesis that Germanic (i.e. Swedish) particles express perfective aspect just like Slavic prefixes, is therefore not supported – Croatian (prefixed) verbs are undoubtedly recognized as perfective or imperfective but aspectual reading of Swedish phrasal verbs can be determined only from their syntactic context, i.e. it depends on other aspectual markers at the syntactic level. The analysis, on the other hand, proves that Swedish particles and Croatian prefixes share lexical characteristics, i.e. both have the ability to express aktionsart. Aktionsart contributes to the aspectual reading of a sentence, but it is not aspect per se. Based on the evidence from the analyzed data the author shows that Verkuyl’s theory of parallelism between Germanic definite objects and Slavic perfective aspect cannot be supported either. In 87% of sentences Swedish transitive phrasal verbs with definite objects are translated into Croatian with perfective verb forms. However, the analysis shows that other elements of the syntactic context (eg. adverbials, conjunctions, verbal tense, aktionsart, etc.) are at least as important for the perfective reading of a Swedish sentence as the presence of a direct object. In other words, direct objects alone are not enough for a Swedish sentence to have the perfective reading. The author concludes that the main difference between Croatian and Swedish aspectual system is that Croatian has both simple (verbal aspect) and compound aspectuality (aktionsart, inherent verbal meaning, syntactic context), whereas Swedish has only compound aspectuality. Therefore Croatian (prefixed) perfective verbs and Swedish phrasal verbs should not be perceived as identical in function. They share a certain number of common characteristics, but the ability to express the verbal aspect is not one of them.